Shifting Corporealities in Contemporary Performance Danger, Im/mobility and Politics (Avant-Gardes in Performance, 2018)
This book investigates how contemporary artistic practices engage with the body and its intersection with political, technological, and ethical issues. Departing from the relationship between corporeality and performing arts (such as theater, dance, and performance), it turns to a pluriversal understanding of embodiment that resides in the extra violent conditions of contemporary global necro-capitalism in order to conduct a thorough analysis that goes beyond arts and culture. It brings together theoretical academic texts by established and emerging scholars alike, exposing perspectives form different fields (philosophy, cultural studies, performance studies, theater studies, and dance studies) as well as from different geopolitical contexts. Through a series of thematic clusters, the study explores the reactivation of the body as a site of a new meaning-making politics.